2012
DOI: 10.1119/1.3678299
|View full text |Cite
|
Sign up to set email alerts
|

Resource Letter ALIP–1: Active-Learning Instruction in Physics

Abstract: This Resource Letter provides a guide to the literature on research-based active-learning instruction in physics. These are instructional methods that are based on, assessed by, and validated through research on the teaching and learning of physics. They involve students in their own learning more deeply and more intensely than does traditional instruction, particularly during class time. The instructional methods and supporting body of research reviewed here offer potential for significantly improved learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
0
15

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 15 publications
6
160
0
15
Order By: Relevance
“…Most studies have reported disappointingly small improvements in student performance on conceptual questions despite direct instruction on the relevant topics [1]. These results have spurred a number of attempts to improve learning in physics courses through new curricula and instructional techniques [2]. This paper contributes to the research base through a retrospective analysis of results from 20 randomly selected qualitative questions on kinematics, dynamics, electrostatics, waves, and physical optics that have been given in introductory calculus-based physics at the University of Washington (UW) over a period of 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported disappointingly small improvements in student performance on conceptual questions despite direct instruction on the relevant topics [1]. These results have spurred a number of attempts to improve learning in physics courses through new curricula and instructional techniques [2]. This paper contributes to the research base through a retrospective analysis of results from 20 randomly selected qualitative questions on kinematics, dynamics, electrostatics, waves, and physical optics that have been given in introductory calculus-based physics at the University of Washington (UW) over a period of 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, different strategies have been implemented by higher education institutions in order to improve the rate of success of first-year undergraduates in science and mathematics courses. Most of these strategies have been focused on implementing active-learning methodologies during lectures to increase motivation and academic success in science and mathematics courses (Meltzer & Thornton, 2012;Paulson, 1999;Prince, 2004). Other approaches, include the implementation of tutoring programs to help students in science and mathematics courses, in a friendly, informal and approachable manner (Báez-Galib et al, 2005;Parsons, 2004).…”
Section: Science and Mathematics Coursesmentioning
confidence: 99%
“…En ellos se propone el aprendizaje activo, dejando el estudiante de tener un papel pasivo, para pasar a ser dinámico y productivo (Meltzer y Thornton, 2012). El acto didáctico ya no tiene un emisor, ya que el alumno puede actuar de emisor y de receptor, el receptor al recibir la información de distintos emisores recibe mayor ri queza.…”
Section: Métodos Basados En La Acción Del Estudianteunclassified